Veterinary Pathology Diseases and Disorders in Domestic and Wild Animals - Arul Sabareeswaran T. A.; Lalremruata, C.; Basheer , Muddasir; Giggin T; Mishra, Manish Raj; Shrivastava , Shruti Mohan; Gupta, Soni; Roy, Deepjyoti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Veterinary pathology plays a crucial role in understanding and managing diseases and disorders in both domestic and wild animals. This field encompasses the study of various pathologies, from infectious diseases like the Spanish Goat Encephalitis Virus, which causes severe neurological symptoms and high mortality in goats, to toxicological conditions such as oleander poisoning in horses, characterized by renal and cardiac lesions. It also includes the investigation of neoplastic conditions, as seen in canine apocrine gland adenocarcinoma of the anal sac and various tumors in African pygmy hedgehogs. The integration of clinical and histopathological findings is essential for accurate diagnosis, treatment, and management of these diverse conditions, highlighting the importance of veterinary pathology in animal health and welfare. Veterinary pathology, a vital branch of veterinary medicine, is instrumental in diagnosing, understanding, and managing a wide array of diseases and disorders in both domestic and wild animals. It encompasses the study of various pathologies, including infectious diseases, toxicological conditions, and neoplastic diseases. For instance, research into the Spanish Goat Encephalitis Virus sheds light on its neurological impact and high mortality rates in goats, while studies on oleander poisoning in horses focus on its renal and cardiac implications. Additionally, the field addresses neoplastic conditions such as canine apocrine gland adenocarcinoma of the anal sac and various tumors in African pygmy hedgehogs. This discipline is not only pivotal in diagnosing and treating these conditions but also plays a significant role in advancing our understanding of animal health and welfare, emphasizing the need for continuous research and collaboration between veterinary clinicians and pathologists.